Nâng cao vai trò tín dụng ngân hàng đối với sự phát triển kinh tế các tỉnh Nam Bộ - Nguyễn, Thị Nhung (2011)
Tác giả: Nguyễn Thị Nhung, TS; Lê Hùng; Lê Thị Thanh Hà; Mai Thị Trúc Ngân; Nguyễn Văn Hà; Nguyễn Văn Lương -- Từ khóa: Tín dụng; Ngân hàng; Nam bộ